2016
DOI: 10.17576/mjas-2016-2006-14
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation Study of Curcumin Into Zinc Layered Hydroxide

Abstract: Zinc layered hydroxide (ZLH) intercalated with curcumin was successfully prepared by ion exchange method. The synthesised nanocomposite was characterised by Powder X-ray diffraction (PXRD) and Fourier transform infrared spectroscopy (FTIR). The obtained intercalation compound, ZLH-curcumin nanocomposite (ZiCUR), showed a basal spacing of 10.0 Å when 0.01M of curcumin solution was used in the synthesis. The shifting in the stretching frequency of the curcumin anion provides strong evidence that the anion is bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several studies have shown that LDH are capable of adsorbing or encapsulating CUR, [ 1,23–28 ] and they have proven to be a potential system of CUR administration in an effective photodynamic therapy, [ 23,28 ] generating apoptosis and autophagy in tumour cells [ 26 ] and presenting antimicrobial activity in bacteria and candids. [ 24 ] However, it is not clear how the composition of the M +2 cation of LDH affects its properties and structure, nor how this influences its biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that LDH are capable of adsorbing or encapsulating CUR, [ 1,23–28 ] and they have proven to be a potential system of CUR administration in an effective photodynamic therapy, [ 23,28 ] generating apoptosis and autophagy in tumour cells [ 26 ] and presenting antimicrobial activity in bacteria and candids. [ 24 ] However, it is not clear how the composition of the M +2 cation of LDH affects its properties and structure, nor how this influences its biological activity.…”
Section: Introductionmentioning
confidence: 99%